Lactobacillus - A Multifunctional Genus 2023
DOI: 10.5772/intechopen.104958
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus Use for Plant Fermentation: New Ways for Plant-Based Product Valorization

Abstract: Today, plant production is increasing, but most industrial processes generate a lot of waste and by-products for which, in the current context, it is a priority to recycle or valorize them. One of the cheapest valorization routes is fermentation, in particular lactic fermentation by Lactobacillus species, which produces lactic acid and other molecules of industrial interest such as bioactive compounds such as anthocyanin, organic acid, peptides, or phenol, which are widely found in the plant matrix, mainly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 110 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Numerous beneficial roles of Lactobacillus casei for the host have been studied, including its potential to reduce cholesterol, exhibit antibacterial activity, and prevent or treat various intestinal diseases 17–19 . Some studies have indicated that using Lactobacillus casei as a starter for herbal fermentation can be a viable method to enhance the efficacy of herbs by increasing the bioactive compounds and improving absorption 20–22 . So, we fermented Amomum xanthioides utilizing Lactobacillus casei under controlled standard conditions, aiming to achieve a synergistic effect on metabolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous beneficial roles of Lactobacillus casei for the host have been studied, including its potential to reduce cholesterol, exhibit antibacterial activity, and prevent or treat various intestinal diseases 17–19 . Some studies have indicated that using Lactobacillus casei as a starter for herbal fermentation can be a viable method to enhance the efficacy of herbs by increasing the bioactive compounds and improving absorption 20–22 . So, we fermented Amomum xanthioides utilizing Lactobacillus casei under controlled standard conditions, aiming to achieve a synergistic effect on metabolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Some studies have indicated that using Lactobacillus casei as a starter for herbal fermentation can be a viable method to enhance the efficacy of herbs by increasing the bioactive compounds and improving absorption. [20][21][22] So, we fermented Amomum xanthioides utilizing Lactobacillus casei under controlled standard conditions, aiming to achieve a synergistic effect on metabolic dysfunction.…”
mentioning
confidence: 99%